Effects of developmental lead exposure on the hippocampal methylome: Influences of sex and timing and level of exposure. (15th June 2018) - Singh, G.; Singh, V.; Wang, Zi-Xuan; Voisin, G.; Lefebvre, F.; Navenot, J-M.; Evans, B.; Verma, M.; Anderson, D.W.; Schneider, J.S.
Highlights: Pb exposure in rats altered the hippocampal methylome at the gene promoter level. These changes are differentially associated with sex, Pb exposure level and timing. Sex is most significantly associated with observed methylation changes. Neural development and function genes were differentially methylated by Pb. Abstract: Developmental lead (Pb) exposure results in persistent cognitive/behavioral impairments as well as an elevated risk for developing a variety of diseases in later life. Environmental exposures during development can result in a variety of epigenetic changes, including alterations in DNA methylation, that can influence gene expression patterns and affect the function and development of the nervous system. The present promoter-based methylation microarray profiling study explored the extent to which developmental Pb exposure may modify the methylome of a brain region, hippocampus, known to be sensitive to the effects of Pb exposure. Male and female Long Evans rats were exposed to 0 ppm, 150 ppm, 375 ppm, or 750 ppm Pb through perinatal exposures (gestation through lactation), early postnatal exposures (birth through weaning), or long-term postnatal exposures (birth through postnatal day 55). Results showed a significant contribution of sex to the hippocampal methylome and effects of Pb exposure level, with non-linear dose response effects on methylation. Surprisingly, the developmental period of exposure contributed only a small amount of variance to the overall data and gene ontology (GO) analysis revealed the largest number of overrepresented GO terms in the groups with the lowest level of exposure. The highest number of significant differentially methylated regions was found in females exposed to Pb at the lowest exposure level. Our data reinforce the significant effect that low level Pb exposure may have on gene-specific DNA methylation patterns in brain and that this occurs in a sex-dependent manner.